Penyesuaian Diri Pada Perempuan Yang Menikah Beda Suku - Djati, Magdalena Daru; Darmawanti, Ira (INCARE, International Journal of Educational Resources, 2024)
Women in interracial marriages tend to face more differences than women in same-race marriages. The differences require women to adjust themselves more. This research aims to examine the process of self-adjustment done by women in interracial marriages. The research approach used was case study. Data was collected using semi-structured interviews to two participants and four significant others. Through the research, it was revealed that the self-adjustment took four forms which were adjustment to their husband, sexual adjustment, financial adjustment, and adjustment to their husband’s family. The self-adjustment was supported by two main factors which were environment and religiosity.